The Influence of Religion on Coping and Adaptation of Families Who Have Children with Disabilities: A Comparison of Christianity and Buddhism Using the Double ABCX Model - Kamei, Ai (Journal of disability & religion, 2014)
In this literature review, the influence of religion on coping abilities of families of children with disabilities will be explored and compared with regard to Christianity and Buddhism. Over the course of adapting to the reality of their new life with a child who has a disability, families often experience psychosocial or existential stress through due to the demands of providing care to the child or by searching for the meaning of why such an event has occurred in their life. This discussion uses the double ABCX model to highlight how religion can contribute to how families cope with stress.